A África do Sul e a resolução de conflitos em África - Luís Castelo Branco (Cadernos de Estudos Africanos)
After the victories of the ANC and Nelson Mandela in the 1994 elections, the international community turned to South Africa in an attempt to find an African partner capable of controlling and leading not only the strategic region of Southern Africa, but the whole African continent. The way in which the transition process had occurred in South Africa, and in particular the key role civil society had played by monitoring it, was considered as a success by the international community. By virtue of the example it had given as well as of the international prestige of some of its leaders, South Africa was as a consequence as a state essential for the stabilization of an unstable continent. In this paper, the author tries to establish up to which point the expectations created with regard to the capacities of South Africa are realistic, in to what degree the international community can at this stage count on a support from South Africa for the resolution of conflicts in Africa.